Adverse Cutaneous Drug Reactions in a Tertiary Care Center Patients: a Prospective Analysis - Sandeep Mahapatra and Umashanker Pd Keshri (Journal of Applied Pharmaceutical Science)
In the dermatology department of a tertiary care centre patients were scrutinized for adverse cutaneous drug reaction and 100 cases of certain and probable causality assessment were studied for type of reaction and their causative agent. Most common morphological pattern observed was maculopapular drug reaction (23%), followed by fixed drug eruption and urticaria 14% and 13% each respectively. Stevens-johnson and toxic epidermal necrolysis accounted for 25%. Pityriasiform, lupus erythematosus like eruption, acute generalized exanthematous pustulosis and dapsone syndrome each accounted for 1%. Most common causative agent observed was NSAID (24%) followed by antibiotics and antiepileptic each in (22%) cases. Other drug responsible for ADR were antiretroviral (6%), antiprotozoals (5%); antimalarials, antitubercular and antihypertensive; each were 4%. It is our contention that the use of high risk drug should be carefully prescribed, monitored and awareness should be created by treating physician so that the morbidity and mortality by the use of the drug should be decreased.
Keywords: Adverse cutaneous drug reaction, fixed drug eruption, stevens-johnson syndrome, toxic epidermal necrolysis.